Designing a Digital Intermediary Platform to Support Micro Business in the Indonesian Event Industry: A Case Study of K-Pop Concertgoers - Aurellio Fishandy; Sonny Rustiadi (Green Publisher Indonesia, 2026)
The rapid growth of the K-pop industry in Indonesia is reflected in its strong cultural influence among Indonesian youth, making the country one of the largest K-pop fan markets globally. This growth is driven not only by high music consumption but also by significant fan spending on related activities, particularly concert attendance. K-pop concerts often require substantial expenses, including tickets, accommodation, merchandise, and supporting services such as make-up artists and phone rentals. The frequency of these transactions has encouraged fans to establish microbusinesses by utilizing their skills, assets, and prior experience. However, the K-pop concert microbusiness ecosystem largely operates informally through fragmented social media platforms without clear regulations or standardized systems, creating challenges such as trust issues, scam risks, unclear coordination, and inconsistent service delivery. This study aims to examine how innovative solutions can be designed to address these challenges and generate value for all stakeholders within the ecosystem. The study employs Empathy Mapping to analyze behaviors and motivations of involved parties, alongside Customer Journey Mapping to examine step-by-step processes and identify pain points at each interaction stage. The findings are translated into innovation concepts using Doblin’s Ten Types of Innovation and the Value Proposition Canvas to ensure alignment with user needs. Finally, Lean Canvas and Minimum Viable Product (MVP) frameworks are applied to translate concepts into implementable solutions. The results indicate that innovation focused on trust-building and coordination standardization plays a critical role in reducing uncertainty, improving service consistency, and supporting long-term business sustainability within the microbusiness ecosystem.